Education in the Republic of South Sudan : Status and Challenges for a New System - World Bank (Washington, DC, 2013)
This education status report (ESR), prepared at the request of the Government of South Sudan (GoSS), provides a comprehensive snapshot of an education sector that is emerging from a long period of civil strife. It confirms the strong appetite among the people for education; in turn, more educated citizens are needed to provide the bedrock of the new country and its prospects. The purpose of this report is to enhance the knowledge base for policy development in the education sector and, more broadly, create a platform for engaging a diverse audience in dialogue on education policies in the new country. The ultimate aim is to help develop a shared vision for the future of the education system among government, citizens, and partners in Africa's newest nation. The report clearly shows that the education system in South Sudan faces all the challenges of a new nation that is making a visible effort to catch up quickly from a very low base by rapidly increasing student enrollment. These challenges include a concentration of students in the early grades; a high proportion of overage students, repetition, and dropout; and weak levels of student learning. Further, the report indicates that South Sudan is beginning to feel the effects of its success at increasing enrollment at the primary level with growing demand for secondary and higher education. The report also highlights the low overall quality of education, and emphasizes that quality of education and accountability of the education sector should become central considerations early on in the development of the education system. Finally, the report emphasizes the importance of South Sudan's unique Alternative Education System (AES), which will continue to play a central part in the education system for years to come. The majority of youth and adults in the country today may never benefit from formal basic education, but their learning needs must be met if South Sudan is to build a solid state and society. The AES is currently offering accelerated learning programs to more than 200,000 youth and adults and holds significant promise.